ПЕРСПЕКТИВЫ СОЗЕРЦАНИЯ МИРА В СЕРБСКОЙ ХУДОЖЕСТВЕННОЙ КУЛЬТУРЕ РУБЕЖА ТЫСЯЧЕЛЕТИЙ (Philological Studies, 2019)
The article is devoted to the metahistory of the modern Slavs which is created in the works by M. Pavich and G. Petrovich. The main constructive element of their metahistory conception is reflecting thought which in slav’s culture is the result of parts jettity of slav’s semantic continuum. Permanent change of it’s extent is ruled by principle of God’s imagination, connected three main activities of organic nature. This principle allows to create the special history of the matter so called universal. The principle of imagination determines the world contemplation perspectives in Serbian art culture. Imagination principle in Pavich’s and Pertrovich’s works includes the following elements: 1) combination of absolute and limited; 2) remaking of universum as fantasy world; 3) acknowledgment the main activities of nonorganic nature as world space dimensions; 4) acknowledgment sensibility, excitability and productive force as world time dimensions; 5) the beings in derivative world have the states which don’t repeat in other environment; 6) in derivative world interval between events is impotent when gravitation, electromagnetic forces are not actual; 7) the history of matter is described by events repeating in works of art culture; 8) the event is understood as series of space and time points marks the reflecting thought as represent of man’s life. The principle of imagination courses the topologic mechanism of influence from future to past what assumes the change of topologic invariants dynamic system external space/ The teleological determination calls forth the construction of art text in Slav’s culture.